The Effect of Increasing Digitalization of Islamic Banking and Digital Financial Literacy on Generation-Z Saving Behavior at Islamic Banks with the Mediating Role of Halal Lifestyle - Azizah, Umul; Mardani, Ronny Malavia; Nurhidayah, Nurhidayah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the effect of digitalization of Islamic banking and digital financial literacy on Generation Z saving behavior, with halal lifestyle as a mediating variable. The study was conducted with an explanatory quantitative approach using AMOS-based Structural Equation Modeling (SEM) analysis techniques. The research respondents were 150 active students of the Faculty of Economics and Business, Islamic University of Malang who have used Islamic bank digital services. The research instrument was prepared based on validated indicators from previous research.The analysis shows that the digitalization of Islamic banking has a positive and significant effect on Generation Z's saving behavior (CR 1.96, p 0.05). Digital financial literacy also has a significant influence on saving behavior, as well as strengthening individual capacity in making financial decisions independently and according to sharia principles. Halal lifestyle is proven to act as a significant partial mediating variable in the relationship between digitalization and saving behavior, as well as between digital financial literacy and saving behavior. This means that the higher the awareness of halal lifestyle, the stronger the relationship between the adoption of Islamic financial technology and sharia-compliant saving habits. The implications of this study emphasize the importance of developing digital services that are not only efficient and secure, but also in line with Islamic religious and ethical values, in order to strengthen the loyalty and financial inclusion of young Muslims. This research also provides a theoretical contribution to the digital technology-based Islamic financial behavioral literature.